The Role of DNA Mismatch Repair and Recombination in the Processing of DNA Alkylating Damage in Living Yeast Cells - Flores-Rozas, Hernan (Adv Biosci Biotechnol, 2015)
It is proposed that mismatch repair (MMR) mediates the cytotoxic effects of DNA damaging agents by exerting a futile repair pathway which leads to double strand breaks (DSBs). Previous reports indicate that the sensitivity of cells defective in homologous recombination (HR) to DNA alkylation is reduced by defects in MMR genes. We have assessed the contribution of different MMR genes to the processing of alkylation damage in vivo. We have directly visualized recombination complexes formed upon DNA damage using fluorescent protein (FP) fusions. We find that msh6 mutants are more resistant than wild type cells to MNNG, and that an msh6 mutation rescues the sensitivity of rad52 strains more efficiently than an msh3 mutation. Analysis of RAD52-GFP tagged strains indicate that MNNG increases repair foci formation, and that the inactivation of the MHS2 and MSH6 genes but not the MSH3 gene result in a reduction of the number of foci formed. In addition, in the absence of HR, NHEJ could process the MNNG-induced DSBs as indicated by the formation of NHEJ-GFP tagged foci. These data suggest that processing of the alkylation damage by MMR, mainly by MSH2-MSH6, is required for recruitment of recombination proteins to the damage site for repair.